PRIORITAS PENGEMBANGAN KOMODITAS TANAMAN PANGAN DI KABUPATEN ROTE NDAO PROVINSI NUSA TENGGARA TIMUR - Chris Natali Namah (Partner, 2020)
Agricultural development aims to increase production to strengthen food availability in order to meet the basic needs of the community in terms of quantity, quality and affordable prices, increase farmers' income by developing agribusiness-oriented farming systems. Food crops are strategic and attractive commodities in relation to the issue of increasing production and guaranteed availability. Food needs continue to increase in line with increasing population. Therefore it is necessary to research on the analysis of the development of food crop commodities using the Location Quotient (LQ) analysis and then to formulate a food crop development strategy that is owned by Rote Ndao District. This research was conducted in Rote Ndao Regency starting from March-October 2018. Data were collected in the form of secondary data and primary data. Data collected in the analysis using Location Quotion (LQ) analysis is then performed with a SWOT analysis to formulate a development strategy. Results obtained: Average food crop production can be explained that each district has a superior commodity (one district and one commodity) based on the highest LQ value, namely: lowland rice commodity in Lobalain sub-district, Paddy fields in Southwest Rote sub-district, Lobalain and Central Rote, Corn in the North West Rote sub-district, Peanuts in the North West Rote sub-district, Green beans in the North West Rote Sub-district and sweet potatoes in the North-West Rote sub-district. The priority strategies that can be carried out in the development of superior food commodities are optimizing agricultural land, diversification of farming in production activities and post-harvest processing activities to absorb available labor, cooperation between marketing of agricultural products, application of farmer selling price information systems, training in eradicating pests and diseases naturally, dealing with droughts and floods, providing online market systems. Keywords: Analysis, Development, Food Crops